Effectiveness of Medical Treatment of Cushing’s Disease: A Systematic Review and Meta-Analysis - Simões Corrêa Galendi, Julia; Correa Neto, Afonso Nogueira Simões; Demetres, Michelle; Boguszewski, Cesar Luiz; Nogueira, Vania dos Santos Nunes (Frontiers in Endocrinology, 2021)
Objective The objective of this systematic review was to evaluate the effectiveness and safety of pasireotide, cabergoline, ketoconazole, levoketoconazole, metyrapone, osilodrostat, and temozolomide for the treatment of Cushing’s disease (CD). Methods The primary outcomes were the proportion of CD control, adverse events (AE), and reduction of urinary free cortisol. Search strategies were applied to Embase, Medline, and CENTRAL. Independent reviewers assessed the study eligibility, extracted data, and evaluated risk of bias. Standardized mean difference was calculated with 95% confidence interval (CI) for continuous data (i.e., pre- and post-intervention). Random meta-analyses for the proportion of CD control and AE were conducted. Results Twenty-nine controlled and non-controlled studies were included. No study with temozolomide and levoketoconazole and one study with osilodrostat fulfilled the inclusion criteria. The meta-analyses of proportion of CD control was 35% for cabergoline (95% CI: 27–43%, six studies, 141 participants), 44% for pasireotide (95% CI: 25–35%, eight studies, 522 participants), 41% for ketoconazole (95% CI: 36–46%, six studies, 450 participants), 66% for metyrapone (95% CI: 46–87%, four studies, 66 participants), and of 66.4% for osilodrostat (95% CI: 57.9, 74.3, 97 participants, one study). One study compared two different treatments (cabergoline vs. ketoconazole), and no statistical difference was observed in CD control (RR: 0.53, 95% CI: 0.15 to 1.87, 14 participants, very low certainty of evidence). The most frequent AE associated with pasireotide was hyperglycemia, dizziness and nausea with cabergoline and metyrapone, and elevated transaminases with ketoconazole. Conclusion The superiority of one drug over another could not be determined due to lack of controlled studies, but the proportion of disease control identified in our meta-analysis may support clinical decision. New therapeutic options should be investigated due to the limited efficacy and tolerability of the currently available medical treatment for patients with Cushing’s disease. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020205567, identifier CRD42020205567.